DIGITALIZATION TRANSFORMATION OF ESD-ORIENTED E-CATALOGUE-BASED BIOLOGY LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES - DianTri Utami; Endah Rita Sulistya Dewi; Ary Susatyo Nugroho (BIOMA : Jurnal Ilmiah Biologi, 2024)
Digitalization transformation in learning refers to the use of information and communication technology to improve the learning and teaching process. In the digital era, teaching materials can be accessed in electronic form. One of the electronic teaching materials that can be used is e-catalog, which is an electronic-based catalog innovation, which is easier to learn anytime and anywhere, cheap and easy to share. However, teaching materials used in learning biology in high school are mostly textbooks that have not been digitized. Various environmental problems that currently arise are not entirely derived from the development of the industrial and technological sectors, but the weak level of human literacy, including attitudes and behaviors towards the environment. This causes the relationship between humans and the environment to be less dynamic. Good environmental education can help raise public awareness about the importance of protecting the environment. Education for Sustainable Development (ESD) is considered necessary to be integrated into the curriculum content and implemented into learning. The purpose of this study is to determine the implementation and effectiveness of ESD-oriented e-catalog-based learning digitalization transformation on the concept of environmental change can improve student learning outcomes. This research method uses a Research and Development (R&D) approach, adapting the ADDIE development model. The ESD-oriented e-catalog on the concept of environmental change has a validity value of 96.40% with a very valid category. The practicality value is 94.56% with a very practical category. The effectiveness value of the N-Gain score for cognitive learning outcomes is 75.12% with a fairly effective category. This ESD-oriented e-catalog can be implemented by being used as a comparison and reference material in developing innovative teaching materials to prepare students for the 21st century.